2022
DOI: 10.3390/metabo12070573
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Profile of Anchusa officinalis L. Differs According to Its Associated Arbuscular Mycorrhizal Fungi

Abstract: Anchusa officinalis (L.) interacts with various microorganisms including arbuscular mycorrhizal fungi (AMF). Recently, the AMF Rhizophagus irregularis MUCL 41833 has been shown to modulate the metabolome of A. officinalis. However, little information is available on the impact that different AMF species may have on primary and secondary plant metabolites. In this study, four AMF species belonging to the genus Rhizophagus (R. irregularis MUCL 41833, R. intraradices MUCL 49410, R. clarus MUCL 46238, R. aggregatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…In Experiment 2, the objective was to evaluate the production of A/Sd and the expression of genes involved in the biosynthetic pathways of A/Sd in A. tinctoria roots colonized (later abbreviated for fluency as M irr , M aggreg , M Rhiz , and M Sept ) or not (NM) with R. irregularis MUCL 41833, R. aggregatus MUCL 49408, the native R. irregularis and S. viscosum and grown for 9 days in the S-H cultivation system. This harvesting time was based on the study of Tsiokanos et al (2022) where different AMF strains were associated to A. officinalis , and plants were harvested after 9 days of growth in the S-H cultivation system. Interesting results were obtained following this harvesting time and therefore considered in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Experiment 2, the objective was to evaluate the production of A/Sd and the expression of genes involved in the biosynthetic pathways of A/Sd in A. tinctoria roots colonized (later abbreviated for fluency as M irr , M aggreg , M Rhiz , and M Sept ) or not (NM) with R. irregularis MUCL 41833, R. aggregatus MUCL 49408, the native R. irregularis and S. viscosum and grown for 9 days in the S-H cultivation system. This harvesting time was based on the study of Tsiokanos et al (2022) where different AMF strains were associated to A. officinalis , and plants were harvested after 9 days of growth in the S-H cultivation system. Interesting results were obtained following this harvesting time and therefore considered in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…(i.e., shoot and root tissues as well as exudates in the nutrient solution), another important Boraginaceae plant, under a semi-hydroponic (S-H) cultivation system (Cartabia et al, 2021). A similar study, conducted with A. officinalis associated with different AMF species (R. irregularis MUCL 41833, Rhizophagus intraradices MUCL 49410, Rhizophagus clarus MUCL 46238, and R. aggregatus MUCL 49408), demonstrated that specific symbiotic associations can affect the production of 10.3389/fmicb.2023.1216029 bioactive compounds differently in the same host (Tsiokanos et al, 2022).…”
Section: Introductionmentioning
confidence: 97%
“…According to the relative abundance of the fragment ions and their retention times, they were identified as 3-and 5-caffeoylquinic acids. In addition, one dicaffeoylquinic acid isomer was also detected with a deprotonated molecular [2] C, [6,7] EV, [24,25] EI, [7,26] O [27] A, [28] EV [29] PA3 Caffeic acid 12.5 226, 298sh, 328 179 135 C, EV A, [2] EV, [24] EI, [26] O [27 [2] C, [6] EI, [26] O [27 A [2] , C [6,7] , EV [24,25] , EI [7,26] , O [27] [2] C, [6] EI, [26] ion at m/z 515 and product ions at m/z 353 (loss of caffeoyl moiety) and at m/z 173 (quinic acid-H 2 O).…”
Section: Characterization and Distribution Of Phenolic Compoundsmentioning
confidence: 99%
“…These AMF-induced changes reflect the influence of AMF on invasive plants, potentially offering a partial explanation for the successful invasion of exotic plants. However, the precise mechanisms through which AMF affects invasive plants remain largely unknown, and the specificity of plant-fungus symbiosis outcomes further complicates the explanation of this mechanism [17][18][19].…”
Section: Introductionmentioning
confidence: 99%